Adnexal mass after subtotal cesarean hysterectomy: Arare case report - Chandanan, Ani; Yadav, Charu; Saxena, Asha; Parmar, Jyotika (Indian Journal of Case Reports, 2026)
Serous cystadenoma is a frequently encountered benign epithelial ovarian tumor in women of reproductive age.Management becomes more challenging in patients with previous pelvic surgeries because of dense adhesions and altered pelvic anatomy. We describe the case of a 31-year-old woman with a prior subtotal cesarean hysterectomy performed for placenta accreta spectrum disorder, who presented with chronic left lower abdominal pain. Radiological imaging demonstrated a multiloculated left adnexal cystic lesion with septations and mural nodularity, raising suspicion of neoplastic pathology. An exploratory laparotomy with adhesiolysis and cyst excision was undertaken successfully. Histopathological examination confirmed serous cystadenoma. This case emphasizes the significance of thorough preoperative assessment, multidisciplinary planning, and careful surgical dissection in patients with complex postoperative pelvic adhesions.